ANALISIS PENGARUH SELF REGULATED LEARNING TERHADAP KEMAMPUAN PENALARAN MATEMATIS SISWA PADA MATERI SPLDV - Restu Rizqia; Eka Senjayawati; Gida Kadarisma (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2022)
This study was conducted based on observations during the implementation of learning during the covid-19 pandemic which showed the low ability of students to master SPLDV materials, considering that it requires independence in studying good self regulated learning. This research aims to analyze the influence of independence in studying science (self regulated learning) on students' mathematical reasoning abilities in SPLDV materials when learning during the covid-19 pandemic. This research was conducted by quantitative methods with a correlational approach. 15 students of class VIII at one of the junior high schools in West Bandung Regency were the subjects in this study. This research was conducted in November during the first semester of the 2021/2022 School Year. Used research instruments are about tests of mathematical reasoning skills, interview guidelines and self regulated learning opinion scales that have been adjusted to their respective indicators. Based on the test results obtained the conclusion that (1) the mathematical reasoning ability of students is influenced by independence in studying the student's self regulated learning. (2) Independence in studying the science (self regulated learning) students positively affect the mathematical reasoning ability of students. (3) The relationship between independence in self regulated learning and mathematical reasoning skills is in a very strong category.